2022
DOI: 10.1002/bse.3188
|View full text |Cite
|
Sign up to set email alerts
|

Doing good for society! How purchasing green technology stimulates consumers toward green behavior: A structural equation modeling–artificial neural network approach

Abstract: Many countries have recognized the urgent need to address environmental problems, such as air pollution, waste disposal, global warming, and natural resource depletion, through the application of green technology. ANT Forest is one such technological initiative that has gained academic attention for its potential to minimize adverse environmental impacts and promote sustainable green behavior by involving people in eco-friendly activities. We built an integrated framework to understand users' continuance inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 119 publications
(281 reference statements)
0
12
0
Order By: Relevance
“…Sun et al, 2016). Ashfaq et al (2023) confirmed in their study that in the context of a green environmental game (ant forest), green habit is positively correlated with perceived green task-technology fit; Gerhart et al (2015) also pointed out that in the context of e-textbooks, habits have a positive impact on the fit between users and e-textbooks. Consistent with previous studies, this study conjects that gaming habits as an individual characteristic also affect the degree of fit between in-vehicle games and user needs.…”
Section: Theoretical Framework Research Hypotheses and Model Establis...mentioning
confidence: 77%
“…Sun et al, 2016). Ashfaq et al (2023) confirmed in their study that in the context of a green environmental game (ant forest), green habit is positively correlated with perceived green task-technology fit; Gerhart et al (2015) also pointed out that in the context of e-textbooks, habits have a positive impact on the fit between users and e-textbooks. Consistent with previous studies, this study conjects that gaming habits as an individual characteristic also affect the degree of fit between in-vehicle games and user needs.…”
Section: Theoretical Framework Research Hypotheses and Model Establis...mentioning
confidence: 77%
“…HTMT criterion is a stringent measure that could detect the possible indiscriminant among the latent variables. Some authors (Ashfaq et al, 2022; Henseler et al, 2015) suggests a threshold of 0.85. As shown from Table 4, all the values were less than 0.85, thus meeting the recommended threshold.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…This phenomenon cannot be denied: it is a pervasive global trend that influences and reshapes value networks over all sectors. Furthermore, the highly dynamic business environment forces organizations to rise up against changing business directives (Han and Trimi, 2022;Ashfaq et al, 2022;Denner et al, 2018;Matt et al, 2015), thus providing answers to the changing customer demands. Actually, digitalization is a complex socio-economic phenomenon that implies important consequences in terms of value added (Baier et al, 2022) and it is important to underline that digitalization is more than digitization, which means to move information into a digital format (Legner et al, 2017).…”
Section: Literature Background 21 Digitalization Phenomenon and Intel...mentioning
confidence: 99%
“…From the theoretical point of view, the study adopted the BPM approach, a holistic way to observe the digitalization phenomenon in SMEs (Chatterjee et al, 2022;Kerpedzhiev et al, 2020;Nambisan et al, 2019), as suggested by Legner et al (2017), and it deepens what is yet unknown in the literature, filling the gap that highlighted a need to investigate about the JIC 25,1 digital tools and BPM relation (Han and Trimi, 2022;Ashfaq et al, 2022;Talwar et al, 2020;Eller et al, 2020;Kerpedzhiev et al, 2020;Antonucci et al, 2020;Denner et al, 2018;Scuotto et al, 2017), under digital transformation lens, because some new challenges are required and coming out (Rajan and Dhir, 2020;Ashurst et al, 2016).…”
Section: Theoretical Contributionmentioning
confidence: 99%
See 1 more Smart Citation